Systems of classification in premodern medical cultures: sickness, health and local epistemologies - Steinert, Ulrike (Medicine and the body in antiquity, 2021)
"Systems of Classification in Premodern Medical Cultures puts historical illness concepts in cross-cultural perspective, investigating perceptions, constructions and experiences of health and illness from antiquity to the 17th century. Focusing on the systematisation and classification of illness in its multiple forms, manifestations and causes, this volume examines case studies ranging from popular concepts illness through to specialist discourses on it. Using philological, historical and anthropological approaches, the contributions cover perspectives across time from East Asian, Middle Eastern and Mediterranean cultures, spanning ancient Egypt, Mesopotamia, Greece and Rome to Tibet and China. They aim to capture the multiplicity of illness concepts and medical traditions within specific societies, and to investigate the historical dynamics of stability and change linked to such concepts. Providing useful material for comparative research, the volume is a key resource for researchers studying the cultural conceptualisation of illness, including anthropologists, historians, and classicists, amongst others."